Speech Act Varieties of Chinese and Non-Chinese Community in Medan Traditional Markets - Vivi Adryani Nasution; Niza Ayuningtias (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
In this study focused on to describing the types and functions of the Tionghoa community utterances that tend to use Hokkien language and the non Tionghoa community that typically to use Indonesian language. The theory proposed by Austin and Leech was used to classify and analyze the speech act data delivered and collected through a non-participative observation and taking notes technique. The data were obtained from five traditional markets in Medan from July to September 2020. The data showed five kinds of speech acts from both the Tionghoa and non-Tionghoa communities. A directive speech act was the dominant speech act obtained because the directive speech act influenced the interlocutor. In this case, the customer dominated the seller to do what the customer demanded. The directive speech act also showed the chief ordering function found in the Tionghoa community, and the bargaining function was located in the nonTionghoa community. The ordering directive speech act prevalent in Tionghoa speakers related to the character of the majority of Tionghoa community members in Medan, which was straightforward. In this case, they gave orders or directly asked for what they needed or sought. Meanwhile, in the non-Tionghoa community, the utterances refer to buying and selling laws, dominated by bargaining utterances, both bargaining for goods or prices. In comparison, the declarative speech act is the minor speech act found to express resignation towards the COVID-19 condition.